Mediation Role of Job Satisfaction on the Effect of Quality of Work Life and Work Engagement on Psychological Well Being: Case Study on Start Up Companies in Malang - Niadianti, Elivia; Sunaryo, Hadi; Asiyah, Siti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to analyze and investigate the effect of quality of work life and work engagement on psychological well being directly, and to know in depth the indirect effect through job satisfaction or in other words mediation. This research was conducted at a start-up company in Malang with a total sample of 71 permanent employees who have worked for more than one year. Collecting data using a questionnaire distributed via google form directly to the research respondents. After the data is collected, then the data is tabulated and coding is done. Then the data was analyzed using structural equation modeling (SEM-PLS) using the help of the Smartpls application version 3. The results of this study indicate that the quality of work life can directly affect job satisfaction and psychological well being, work engagement can increase job satisfaction and psychological well being directly, job satisfaction can directly improve psychological well being, furthermore job satisfaction is able to mediate the influence between quality of work life and work engagement on psychological well being.